An introduction to Catholicism - Cunningham, Lawrence (Cambridge, UK ; New York : Cambridge University Press, 2009)
This account goes back to the early Christian creeds to uncover the roots of modern Catholic thinking. It avoids theological technicalities, and throws light on aspects of the Church's institutional structure and liturgical practice that even Catholics can find baffling: Why go to confession? How are people made saints? What is 'infallible' about the Pope?--P. [4] of cover.
The many meanings of Catholicism -- Roman Catholicism -- Being Catholic : some typologies -- Catholicism in place and time -- Catholic worship -- The rule of faith -- Catholic spirituality -- The missionary character of Catholicism -- Catholic reformation(s) -- The moral life -- The contemporary Catholic Church.
"Reading Catholicism : bibliographical resources": p. 269-275.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Catholic Church; Katholizismus; RELIGION / Christianity / Catholic; Lehrbuch; Electronic books